2022
DOI: 10.1002/chem.202201209
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Bond Enhanced Lithium Halide Ion‐Pair Binding by Halogen Bonding Heteroditopic Rotaxanes**

Abstract: A family of novel halogen bonding (XB) and hydrogen bonding (HB) heteroditopic [2]rotaxane host systems constructed by active metal template (AMT) methodology, were studied for their ability to cooperatively recognise lithium halide (LiX) ion-pairs. 1 H NMR ion-pair titration experiments in CD 3 CN:CDCl 3 solvent mixtures revealed a notable "switch-on" of halide anion binding in the presence of a cobound lithium cation, with rotaxane hosts demonstrating selectivity for LiBr over LiI. The strength of halide bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…[92] On the other hand, Beer and co-workers have prepared a series of novel heteroditopic [2]rotaxane type receptors, displaying lithium salt ion-pair recognition, via triazole based halogen as well as hydrogen bonding interactions in both the axle and macrocycle units (Figure 16). [94] From the analysis of spectroscopy and DFT studies, it was clearly observed that the MIM systems 127-129 displayed higher binding affinity with lithium halides as compared to the non-interlocked macrocyclic systems of same components. Interestingly, it was found that the binding of Li + was found to polarize the halogen bond donors and preorganize the anion binding sites, thereby leading to the cation-induced switch on of the cooperative halide recognition.…”
Section: Ion-pair Receptor Molecular Machinesmentioning
confidence: 99%
“…[92] On the other hand, Beer and co-workers have prepared a series of novel heteroditopic [2]rotaxane type receptors, displaying lithium salt ion-pair recognition, via triazole based halogen as well as hydrogen bonding interactions in both the axle and macrocycle units (Figure 16). [94] From the analysis of spectroscopy and DFT studies, it was clearly observed that the MIM systems 127-129 displayed higher binding affinity with lithium halides as compared to the non-interlocked macrocyclic systems of same components. Interestingly, it was found that the binding of Li + was found to polarize the halogen bond donors and preorganize the anion binding sites, thereby leading to the cation-induced switch on of the cooperative halide recognition.…”
Section: Ion-pair Receptor Molecular Machinesmentioning
confidence: 99%
“…The design and synthesis of high-performance receptors for Li + have traditionally focused on developing macrocyclic receptors, featuring small binding cavities meticulously tailored 19,20,23–30 to selectively bind Li + while excluding competing ions such as sodium (Na + ) and potassium (K + ). A pioneering work in this domain was exemplified 31–36 by Donald Cram's spherands, which displayed an extraordinary binding affinity exceeding 10 16 M −1 for Li + due to their rigid and preorganized binding cavities.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Consequently, the design and implementation of molecular receptors capable of effectively recognizing, sensing, extracting, and purifying this critical mineral have become paramount in addressing this pressing challenge. [16][17][18][19][20][21][22] The design and synthesis of high-performance receptors for Li + have traditionally focused on developing macrocyclic receptors, featuring small binding cavities meticulously tailored 19,20,[23][24][25][26][27][28][29][30] to selectively bind Li + while excluding competing ions such as sodium (Na + ) and potassium (K + ). A pioneering work in this domain was exemplied [31][32][33][34][35][36] by Donald Cram's spherands, which displayed an extraordinary binding affinity exceeding 10 16 M −1 for Li + due to their rigid and preorganized binding cavities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] We and others have demonstrated that anion recognition strategies employing exotic sigma-hole based interactions, [18][19][20][21][22][23] including halogen bonding (XB), [24][25][26][27][28][29][30][31] engender considerable advantages over more traditional approaches, such as hydrogen bonding (HB). Furthermore, while rare, the few reports [32][33][34][35][36][37] of XB integration in heteroditopic receptor design have also revealed unique behavior. In particular, XB mediated anion binding potency can be effectively 'switched on' by an inductive effect of a co-bound alkali metal cation, polarizing a proximal CÀ I XB donor, which constitutes a novel and interesting mechanism of cooperativity.…”
Section: Introductionmentioning
confidence: 99%